ADRB2 polymorphism Arg16Gly modifies the natural outcome of heart failure and dictates therapeutic response to β-blockers in patients with heart failure. Issue 1 (December 2018) - Huang, Jin; Li, Chenze; Song, Ying; Fan, Xiaohan; You, Ling; Tan, Lun; Xiao, Lei; Li, Qing; Ruan, Guoran; Hu, Senlin; Cui, Wei; Li, Zongzhe; et al.
Abstract We sought to investigate the association of single nucleotide polymorphisms (SNPs) of the genes involved in βAR signaling with the response of patients to βAR blockers. A total of 2403 hospitalized patients with chronic heart failure (HF) were enrolled in a multicenter observational study as the first cohort and followed up for a mean period of 20 months. Genes for β1AR, β2AR, and the major cardiac G-protein-coupled receptor kinases (GRKs)GRK2 andGRK5 were analyzed to identify SNPs, and patients were stratified according to genotypes. A second independent cohort enrolling 919 patients with chronic HF was applied to validate the observed associations. The signaling properties of the key identified SNPs were assessed in vitro. Our data showed that HF patients harboring the Gly16 allele in the gene for β2AR (ADRB2 ) had an increased risk of the composite end point relative to patients who were homozygous for Arg16. Notably, these patients showed a beneficial response to βAR-blocker treatment in a G allele-dose-dependent manner, whereas Arg16 homozygotes had no response to βAR-blocker therapy. This Arg16Gly genotype-dependent heterogeneity in clinical outcomes of HF was successfully validated in the second independent population. Besides, the in vitro experiments revealed that G allele carriers were defective in β2AR-coupled inhibitory adenylate cyclase g (Gi ) protein signaling.